Extent of Exclusions for Chronic Conditions in Breast Cancer Trials. Issue 4 (11th December 2018) - Kronish, Ian M; Fenn, Kathleen; Cohen, Laura; Hershman, Dawn L; Green, Paige; Jenny Lee, Sung A; Suls, Jerry
Abstract: Experts have expressed concerns that patients with chronic conditions are being excessively excluded from cancer randomized clinical trials (RCTs), limiting generalizability. Accordingly, we queried clinicaltrials.gov to determine the extent to which patients with chronic conditions were excluded from phase III cancer trials, using National Cancer Institute-sponsored breast cancer RCTs as a test case. Two physicians independently coded for the presence of 19 prevalent chronic conditions within eligibility criteria. They also coded for exclusions based on performance status and vague criteria that could have broadly excluded patients with chronic conditions. The search identified 58 RCTs, initiated from 1993 to 2012. Overall, 88% of trials had at least one exclusion for a chronic condition, performance status, or vague criterion. The three most commonly excluded conditions were chronic kidney disease, heart failure, and ischemic heart disease. Our study demonstrated that patients with prevalent chronic conditions were commonly excluded from National Cancer Institute-sponsored RCTs.